Hearing loss and risk of depressive symptoms in older adults in the Health ABC study - Powell, Danielle S.; Betz, Joshua F.; Yaffe, Kristine; Kritchevsky, Stephen; Strotmeyer, Elsa; Simonsick, Eleanor M.; Rubin, Susan; Houston, Denise K.; Pratt, Sheila R.; Purchase Helzner, Elizabeth; Brewster, Katharine K.; Lin, Frank R.; et al. (Frontiers in Epidemiology, 2022)
Objective Hearing loss (HL) is highly prevalent among older adults and may lead to increased risk of depressive symptoms. In both cross-sectional and longitudinal analysis, we quantified the association between HL and depressive symptoms, incorporating the variable nature of depressive symptoms and characterizing by race and gender. Methods Data were from the Health, Aging, and Body Composition study. Depressive symptoms were measured using the Center for Epidemiologic Study Depression Scale short form (CES-D 10), defined as CES-D 10 score ≥10 or treatment for depression. Hearing was defined via four-frequency pure-tone average (PTA) decibel hearing level (dB HL), categorized as normal hearing (PTA ≤25 dB HL), mild HL (PTA26-40 dB HL), and ≥moderate HL (PTA > 40 dB HL). Associations at baseline were quantified using logistic regression, incident depressive symptoms using Cox proportional hazard models, and change in depressive symptoms over time using growth mixture models and multinomial logistic regression. Results Among 2,089 older adults (1,082 women, 793 Black; mean age 74.0 SD: 2.8), moderate or greater HL was associated with greater odds of concurrent [Odds Ratio (OR):2.45, 95% CI:1.33, 4.51] and incident depressive symptoms [Hazard Ratio (HR):1.26, 95% CI:1.00, 1.58]. Three depressive symptom trajectory patterns were identified from growth mixture models: low, moderate increasing, and borderline high depressive symptom levels. Those with moderate or greater HL were more likely to be in the borderline high depressive-symptom trajectory class than the low trajectory class [Relative Risk Ratio (RRR):1.16, 95% CI:1.01, 1.32]. Conclusions HL was associated with greater depressive symptoms. Although findings were not statistically significantly different by gender and race, estimates were generally stronger for women and Black participants. Investigation of psychosocial factors and amelioration by hearing aid use could have significant benefit for older adults' quality of life.